2017
DOI: 10.1186/s12954-017-0187-5
|View full text |Cite
|
Sign up to set email alerts
|

A critique of the US Surgeon General’s conclusions regarding e-cigarette use among youth and young adults in the United States of America

Abstract: Background: In December 2016, the Surgeon General published a report that concluded e-cigarette use among youth and young adults is becoming a major public health concern in the United States of America. Methods: Re-analysis of key data sources on nicotine toxicity and prevalence of youth use of e-cigarettes cited in the Surgeon General report as the basis for its conclusions. Results: Multiple years of nationally representative surveys indicate the majority of e-cigarette use among US youth is either infreque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 73 publications
0
20
0
Order By: Relevance
“…Longitudinal cohort studies (‘prospective studies’) are promising, because they can demonstrate whether and how trajectories of smoking initiation differ between e‐cigarette users and non‐users. However, there are difficulties in making causal inferences using this approach . Some of these, such as a lack of sufficient attention to measures of the type and intensity of cigarette use and e‐cigarette use , could potentially be overcome.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Longitudinal cohort studies (‘prospective studies’) are promising, because they can demonstrate whether and how trajectories of smoking initiation differ between e‐cigarette users and non‐users. However, there are difficulties in making causal inferences using this approach . Some of these, such as a lack of sufficient attention to measures of the type and intensity of cigarette use and e‐cigarette use , could potentially be overcome.…”
mentioning
confidence: 99%
“…However, there are difficulties in making causal inferences using this approach . Some of these, such as a lack of sufficient attention to measures of the type and intensity of cigarette use and e‐cigarette use , could potentially be overcome. Nonetheless, never‐smokers who try e‐cigarettes are likely to be very different from never‐smokers who do not.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative surveys cannot, for the most part, explore these more nuanced aspects of ecigarette/vape use and yet these are precisely the domains that we need to better understand in order to develop evidence-based interventions aimed at reducing the use of these devices by non-smokers. Large scale social surveys of young people that report substantial increases in e-cigarette/vape use are often based on 'ever' or 'last 30 day' measures (27). However, survey work with young people have also shown that only a tiny proportion of ever users report frequent or current use of these devices (7,27,28,29,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Large scale social surveys of young people that report substantial increases in e-cigarette/vape use are often based on 'ever' or 'last 30 day' measures (27). However, survey work with young people have also shown that only a tiny proportion of ever users report frequent or current use of these devices (7,27,28,29,30,31). Quantitative surveys need measures that better capture the quantity and frequency of use of e-cigarette and vape devices and other important variables like nicotine content (11).…”
Section: Discussionmentioning
confidence: 99%